A Multiplatform Experiment to Unravel Meso- and Submesoscale Processes in an Intense Front (AlborEx) - Pascual, Ananda; Ruiz, Simon; Olita, Antonio; Troupin, Charles; Claret, Mariona; Casas, Benjamin; Mourre, Baptiste; Poulain, Pierre-Marie; Tovar-Sanchez, Antonio; Capet, Arthur; Mason, Evan; Allen, John T.; et al. (Frontiers in Marine Science, 2017)
The challenges associated with meso- and submesoscale variability (between 1-100 km) require high-resolution observations and integrated approaches. Here we describe a major oceanographic experiment designed to capture the intense but transient vertical motions associated with mesoscale and submesoscale features in an area characterized by strong fronts. Finescale processes were studied in the eastern Alboran Sea (Western Mediterranean) about 400 km east of the Strait of Gibraltar, a relatively sparsely sampled area. In-situ systems were coordinated with satellite data to provide a full description of the physical and biogeochemical variability. Hydrographic data confirmed the presence of an intense salinity front formed by the confluence of Atlantic Waters, entering from Gibraltar, with the local Mediterranean waters. The drifters coherently followed the northeastern limb of an anticyclonic gyre. Near real time data from acoustic current meter data profiler showed consistent patterns with currents of up to 1m/s in the southern part of the sampled domain. High-resolution glider data revealed submesoscale structures with tongues of chlorophyll-a and oxygen associated with the frontal zone. Numerical results show large vertical excursions of tracers that could explain the subducted tongues and filaments captured by ocean gliders. A unique aspect of AlborEx is the combination of high-resolution synoptic measurements of vessel-based measurements, autonomous sampling, remote sensing and modeling, enabling the evaluation of the underlying mechanisms responsible for the observed distributions and biogeochemical patchiness. The main findings point to the importance of fine-scale processes enhancing the vertical exchanges between the upper ocean and the ocean interior.